Impact of proton implantation parameters on the photoconductivity of photorefractive multiple quantum wells - Jabłoński, Błażej; Branecka, Agnieszka; Miśkiewicz, Eliza; Ziółkowski, Andrzej; Weinert-Rączka, Ewa (Photonics Letters of Poland, 2015)
<!– saved from url=(0022)http://internet.e-mail –> Semi-insulating GaAs/AlGaAs multiple quantum wells are photorefractive materials with high sensitivity and a short response time. Semi-insulation of these structures is commonly obtained by proton implantation. We present the measurements of photoconductivity in the samples with different proton doses. The results were compared to the theoretically predicted relationship between photoconductivity and the donor to acceptor concentration ratio. This allows to estimate the impact of proton dose on deep donor concentration. Full Text: PDF References D.D. Nolte, "Semi-insulating semiconductor heterostructures: Optoelectronic properties and applications", J. Appl. Phys. 85, 6259 (1999). CrossRef D.D. Nolte, M.R. Melloch, in Photorefractive effects and Materials, ed. D.D. Nolte (Kluwer, Dordrecht, 1995). CrossRef Q. Wang, R.M. Brubaker, D.D. Nolte, M.R. Meloch, "Photorefractive quantum wells: transverse Franz–Keldysh geometry", J. Opt. Soc. Am. B 9, 1626 (1992). CrossRef Q. Wang, RM. Brubaker, D.D. Nolte, "Photorefractive phase shift induced by hot-electron transport: multiple-quantum-well structures", J. Opt. Soc. Am. B 11, 1773 (1994). CrossRef M. Wichtowski, A. Ziolkowski, E. Weinert-Rączka, "A general approach to the space?charge field solution in photorefractive materials in a TWM geometry", J. Opt. 12, 065201 (2010). CrossRef A. Ziółkowski, "Self-bending of light in photorefractive semiconductors with hot-electron effect", Opt. Expr. 22, 4599 (2014). CrossRef K. Seeger, Semiconductors Physics, fifth ed., Chapter 1 (Springer-Verlag, Berlin, 1991). CrossRef S.M. Sze, Physics of Semiconductors Devices, Second ed., Chapter 1 (Wiley, New York, 1981). S. Balasubramanian, I. Lahiri, Y. Ding, M.R. Melloch, D.D. Nolte, "Two-wave-mixing dynamics and nonlinear hot-electron transport in transverse-geometry photorefractive quantum wells studied by moving gratings", Appl. Phys. B 68, 863 (1999). CrossRef P. Yeh in Introduction to Photorefractive Nonlinear Optics, (Wiley, New York, 1993). CrossRef